Improvement of the nutritive value of palm kernel cake by fungal and extrusion treatments - Fam, Jye Ping (2015)
Palm kernel cake (PKC) is an agro-industrial by-product used widely as animal feed, but has limitated use in poultry feeds due to its high fibre content. The objective of the project was to enhance the nutritive value of PKC through solid state fermentation (SSF) using the fungus Rhizopus oligosporus and extrusion. In this study, central composite design (CCD) of response surface methodology (RSM) was used to design the fermentation conditions. Four independent variables investigated were moisture content, incubation time, temperature, and inoculum density. Thirty runs with different fermentation conditions were evaluated to treat PKC with R. oligosporus, and to measure the interested responses (reducing sugar, soluble protein, crude fibre and neutral detergent fibre). Through the CCD approach, the results were used to produce second order polynomial equations for each response to proceed to the optimization of fermentation condition. The optimized fermentation conditions were moisture level of 68.7 ml/50 g substrate, incubation duration of 5.9 days, incubation temperature of 34°C and inoculum density of 1x107 spore/ml. Under optimized condition, the nutritive values of fermented PKC were 8.25±0.04 mg/g of reducing sugar, 10.48±0.66 mg/g of soluble protein, 15.9±0.78 % of crude fibre, 57.6±0.495 % of neutral detergent fibre as compared to 7.77±0.25 mg/g of reducing sugar, 2.88±0.16 mg/g of soluble protein, 20.42±0.98 % of crude fibre and 73.7±0.72 % of neutral detergent fibre for unfermented PKC. Extruded PKC was also used as substrate for SSF under optimized fermentation condition. The reducing sugar and soluble protein content of fermented extruded-PKC has increased 80.9 % and 138.5 % , while crude fibre and neutral detergent fibre has decreased 23.4% and 23.6%, respectively, as compared to unfermented extruded-PKC. The results showed that the nutritive value of PKC was enhanced by solid state fermentation with R. oligosporus, while extrusion process did not improve fermentation further to enhance the nutritive value of PKC.